First Organoid Intelligence (OI) workshop to form an OI community - Morales Pantoja, Itzy E.; Smirnova, Lena; Muotri, Alysson R.; Wahlin, Karl J.; Kahn, Jeffrey; Boyd, J. Lomax; Gracias, David H.; Harris, Timothy D.; Cohen-Karni, Tzahi; Caffo, Brian S.; Szalay, Alexander S.; Han, Fang; et al. (Frontiers in Artificial Intelligence, 2023)
technology, bioengineering, and machine learning, we can explore the ability of brain organoids to compute, and store given information (input), execute a task (output), and study how this affects the structural and functional connections in the organoids themselves. Furthermore, understanding how learning generates and changes patterns of connectivity in organoids can shed light on the early stages of cognition in the human brain. Investigating and understanding these concepts is an enormous, multidisciplinary endeavor that necessitates the engagement of both the scientific community and the public. Thus, on Feb 22-24 of 2022, the Johns Hopkins University held the first Organoid Intelligence Workshop to form an OI Community and to lay out the groundwork for the establishment of OI as a new scientific discipline. The potential of OI to revolutionize computing, neurological research, and drug development was discussed, along with a vision and roadmap for its development over the coming decade.